Identification of Cyber Crimes in Turkey and Content Analysis For Infringements - Metin Turan; Özgür Külcü (Türk Kütüphaneciliği)
The development of information technologies and information systems brings also about an increase of violations in this area. In this study, cybercrimes within the scope information technology law, are, by means of content analysis of Supreme Court’s Decisions, examined. Within this framework, considerations such as their subjects, features, application conditions of laws, problems occurred and defective points are addressed. As a result of the analysis, the provisions of the law violated are stated with the reasons. Provisions related to cybercrimes in the law number 5237 the Turkish Criminal Code constitute main frame of the study. At the end of the analysis, it was deduced that violations mainly occurred within the framework of the articles 244 and 245th.